The efficacy of tualang honey as wound dressing of full-thickness wound in animal model - Wan Azman, Wan Sulaiman (Pusat Pengajian Sains Perubatan, 2012)
We conducted this study to compare the specificity and sensitivity of the Ortolani and Barlow tests performed by dedicated examiners with routine ecxarniner, and to ascertain the incidence of developmental dysplasia of the hip (DDH) in breech babies. Methods: A dedicated examiner underwent specific training and testing by a paediatric orthopaedic surgeon. Routine examiners were medical officers who had basic training in medical school and were briefly trained by their superiors. The dedicated examiner examined 170 babies. Thirty babies including 5 babies with positive tests (according to the dedicated examiner) were examined by a blinded routine examiner. Results of Ortolani and Barlow tests on 30 babies were compared with ultrasound examination by blinded radiologist. Results: Five babies had positive Ortolani and Barlow tests. The routine examiner did not detect positive Ortolani and Barlow tests. Conclusion:The incidence of positive Ortolani and Barlow tests among breech babies was 2.8%. Result of Ortolani and Barlow tests by dedicated hip screener were better than results performed by routine examiner.